Radiation and adjuvant drug-loaded liposomes target glioblastoma stem cells and trigger in-situ immune response. Issue 1 (18th June 2021) - Pizzocri, Marco; Re, Francesca; Stanzani, Elisabetta; Formicola, Beatrice; Tamborini, Matteo; Lauranzano, Eliana; Ungaro, Federica; Rodighiero, Simona; Francolini, Maura; Gregori, Maria; Perin, Alessandro; DiMeco, Francesco; et al.
Abstract: Background: The radio- and chemo-resistance of glioblastoma stem-like cells (GSCs), together with their innate tumor-initiating aptitude, make this cell population a crucial target for effective therapies. However, targeting GSCs is hardly difficult and complex, due to the presence of the blood–brain barrier (BBB) and the infiltrative nature of GSCs arousing their dispersion within the brain parenchyma. Methods: Liposomes (LIPs), surface-decorated with an Apolipoprotein E-modified peptide (mApoE) to enable BBB crossing, were loaded with doxorubicin (DOXO), as paradigm of cytotoxic drug triggering immunogenic cell death (ICD). Patient-derived xenografts (PDXs) obtained by GSC intracranial injection were treated with mApoE-DOXO-LIPs alone or concomitantly with radiation. Results: Our results indicated that mApoE, through the engagement of the low-density lipoprotein receptor (LDLR), promotes mApoE-DOXO-LIPs transcytosis across the BBB and confers target specificity towards GSCs. Irradiation enhanced LDLR expression on both BBB and GSCs, thus further promoting LIP diffusion and specificity. When administered in combination with radiations, mApoE-DOXO-LIPs caused a significant reduction of in vivo tumor growth due to GSC apoptosis. GSC apoptosis prompted microglia/macrophage phagocytic activity, together with the activation of the antigen-presenting machinery crucially required for anti-tumor adaptive immune response. Conclusions: Our results advocate for radiotherapy and adjuvant administration of drug-loaded, mApoE-targeted nanovectors as an effective strategy to deliver cytotoxic molecules to GSCs at the surgical tumor margins, the forefront of glioblastoma (GBM) recurrence, circumventing BBB hurdles. DOXO encapsulation proved in situ immune response activation within GBM microenvironment.